The Stable Algorithm Based on a Model Reference Adaptive Control for the Dual Star Machine Drive, ISSN 1582-4594 - Laamayad tahar; Naceri Farid (Journal of Electrical Engineering, Rouma, 2015)
This paper deals with the design and a simulations study of a Model Reference Adaptive Control speed adaptive controller used for control Dual Star Induction Machine, The developed controller is designed in accordance with Lyapunov stability theory. The technique proposed gives fast dynamic response with no overshoot, the simulation results show that the control.